1990
DOI: 10.1557/proc-185-209
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Better Understanding of B72 Acrylic Resin/Methyltrimethoxysilane Stone Consolidants

Abstract: B72 acrylic resin/methyltrimethoxysilane (YMTMOS) mixtures are frequently employed as consolidants for deteriorated limestones, sandstones and marbles- The addition of B72 to MTMOS imparts adhesive properties to the consolidant but it is not known to what degree the B72 affects the reactions which MTMOS must undergo to form a solid polymer network. This paper examines the following chemical, physical, and mechanical properties in order to better understand B72/MTMOS systems: 1. viscosity 2. vapor pressure 3. r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…3d shows that the alcohol was not found in the pre-solution added with PEG 2000 at pH 9 even with the aging time of 81 h. Overall, the presence of PEG increases the degree of hydrolysis and condensation of the TEOS pre-solutions at pH 3 and pH 9 (except pre-solution with addition of PEG 2000 at pH 9). These results are similar to that reported by Wheeler et al [29]. They found that polyacrylate could promote the degree of condensation of TEOS.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…3d shows that the alcohol was not found in the pre-solution added with PEG 2000 at pH 9 even with the aging time of 81 h. Overall, the presence of PEG increases the degree of hydrolysis and condensation of the TEOS pre-solutions at pH 3 and pH 9 (except pre-solution with addition of PEG 2000 at pH 9). These results are similar to that reported by Wheeler et al [29]. They found that polyacrylate could promote the degree of condensation of TEOS.…”
Section: Resultssupporting
confidence: 92%
“…Heteronuclear decoupling was not employed in order to retain proton multiplets for better presenting the evolution of the spectral pattern. In addition, the liquid 13 C and 29 Si NMR measurements were performed on a Bruker 300 MHz NMR spectrometer with the resonance frequency of 75.47 MHz for 13 C and 59.63 MHz for 29 Si, respectively. To obtain sufficient signal intensity, 128 scans were acquired for each 13 C NMR spectrum with a 2 s recycle delay using a 30°pulse angle and 9000 scans were acquired for each 29 Si NMR spectrum with a 5 s recycle delay using a 30°pulse.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations